Coggle's Role in Sharpening Students' Critical Thinking in Islamic Religious Education Learning - Puspaningrum, Diah Puspaningrum; Ismail, Ismail; Ruswan, Ruswan (Journal of Islamic Studies and Civilization, 2025)
The digital era has led to the growing integration of technology in education, including Islamic Religious Education. Visual organizer applications such as Coggle offer great potential for improving learning effectiveness and students' critical thinking skills. However, its use in the context of Islamic Religious Education is still limited, so more in-depth research is needed to explore its benefits and implications more broadly. Therefore, this study was conducted to further analyze the use of Coggle in building students' critical thinking skills in PAI lessons at SMAN 3 Semarang. Based on the results of observations, interviews, and document studies, this study found that Coggle was proven to be effective in helping students break down complex PAI material into a more structured form, visualize the relationships between concepts, and encourage them to analyze and conclude information. The collaborative process of creating concept maps also allows students to evaluate their own understanding by comparing different points of view. In conclusion, the use of Coggle not only deepens students' understanding of PAI material, but also hones critical thinking skills that can be applied in other subjects. The integration of Coggle into PAI learning is highly recommended as an innovative step to create an interactive learning environment and produce a critical and creative generation.